Antimicrobial resistant bacteria in production animals in Iceland. Possible transmission to humans? - Þórunn Rafnar Þorsteinsdóttir 1979- (2009)
Antimicrobial resistance is a growing problem in human as well as veterinary medicine. Antimicrobial resistance rates of bacteria from production animals and their food products are available for many countries but until now little has been known about the prevalence in Iceland. The main objective of this study was to determine the prevalence of antimicrobial resistant bacteria (Salmonella spp., Campylobacter spp. and Escherichia coli) in production animals in Iceland and if these resistant bacteria were transferred from animals to humans, possibly through food. A total of 163 Salmonella strains and 362 Campylobacter strains, isolated from broilers and pigs in the national Salmonella and Campylobacter surveillance programmes in the years 2001-2005, were available for study. A total of 482 E. coli isolates from healthy pigs, broiler chicken, pork, broiler meat, broiler feed, slaughterhouse personnel and outpatients in the years 2005-2008 were collected and tested. Isolates were tested for antimicrobial susceptibility using a microbroth dilution method (VetMIC) and resistant strains were compared using Pulsed Field Gel Electrophoresis (PFGE), Randomly Amplified Polymorphic DNA (RAPD) and phage typing. The overall prevalence of resistance among Salmonella spp. was 13.6% in chickens and 12.8% in pigs. Twenty one isolates (12.8%) were resistant to one or more antimicrobials, 19 S. Typhimurium strains, one S. Infantis strain and one S. Worthington strain. Of the 19 resistant S. Typhimurium strains, 16 were multiresistant (to ≥3 antimicrobial agents) and of these 15 had identical or closely related PFGE patterns and were of phage type DT 104. The prevalence of resistance among Campylobacter isolates was 6.9%, although none were multiresistant. Resistance to ampicillin was most commonly observed (3.6%) followed by resistance to enrofloxacin (3%), nalidixic acid (1.9%) and oxytetracyclin (0.3%), with cross-resistance between enrofloxacin and nalidixic acid. Resistance rates among C. coli isolates (53.8%) were much higher ...